2020
DOI: 10.4187/respcare.07487
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Sitting Out of Bed and Exercise on Lung Aeration and Oxygenation in Critically Ill Subjects

Abstract: BACKGROUND: Early mobilization during critical illness is safe and has beneficial effects on functional outcomes. However, its impact on pulmonary function has not been thoroughly explored. We hypothesized that a sitting position out of bed coupled with exercise could result in an improvement in oxygenation and lung aeration. METHODS: The study was conducted on a cohort of adult subjects within a week of their admission to an ICU. Subjects were transferred to a chair and undertook a 15-min session of exercise,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
7
0
3
Order By: Relevance
“…As the resilience of mechanically ventilated patients is usually lower, early mobilization for these patients consists of lighter and shorter exercises and is therefore not necessarily comparable to the training we chose for our study. Hickmann et al (2021) showed that an upright position and early mobilization improved ventilation distribution and gas exchange especially in severely hypoxemic subjects, some of whom were also mechanically ventilated. Thus, it remains unclear whether the effects we observed in our study might have been different in patients with severely impaired gas exchange.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the resilience of mechanically ventilated patients is usually lower, early mobilization for these patients consists of lighter and shorter exercises and is therefore not necessarily comparable to the training we chose for our study. Hickmann et al (2021) showed that an upright position and early mobilization improved ventilation distribution and gas exchange especially in severely hypoxemic subjects, some of whom were also mechanically ventilated. Thus, it remains unclear whether the effects we observed in our study might have been different in patients with severely impaired gas exchange.…”
Section: Discussionmentioning
confidence: 99%
“… Schujmann et al (2020) showed that patients who participated in an ICU mobility program, whose protocol included mobilization to standing position, had a better functional outcome at discharge than the control group. Hickmann et al (2021) showed that sitting in combination with active exercise resulted in better lung aeration. The question arises whether mobilization into standing brings a significant additional gain during physiotherapy than just sitting.…”
Section: Discussionmentioning
confidence: 99%
“…16,20 Nossos resultados revelam que a sedestação (91,2%) foi a intervenção para MP mais citada pelos participantes. Segundo Hickmann et al 21 , quando acompanhada de exercícios ativos, otimiza a aeração pulmonar e minimiza a hipoxemia.…”
Section: Discussionunclassified
“…Importantly, sitting out of bed itself is the major achievement offered by such a program. This posture is associated with improved oxygenation and respiratory mechanics [22,23]. Further, this posture requires substantial truncal tone and early mobilization cohort (mean, 1.2; SD, 1.5); and upon discharge in control group (mean, 1.8; SD, 1.8) and early mobilization group (mean, 4.9; SD, 2.9).…”
Section: Defining Earliness In Early Mobilizationmentioning
confidence: 99%